Sulbactam-based therapy for Acinetobacter baumannii infection: a systematic review and meta-analysis - Chu,Haiqing (2013)
BACKGROUND: A number of studies have reported on the effectiveness of sulbactam-based therapies for Acinetobacter baumannii infection; however, there is little evidence that sulbactam-based therapies are more or less effective than alternative therapies. Unfortunately, there is a distinct lack of high quality data (i.e., from randomized controlled trials) available on this issue. Therefore, we conducted a systematic review and meta-analysis comparing the efficacy of sulbactam-based and non-sulbactam-based regimens in the treatment of A. baumannii infection. METHODS: We searched PubMed, MEDLINE, Biomedical Central, Google Scholar, the China National Knowledge Infrastructure, the Cochrane library, and the Directory of Open Access using the terms "sulbactam and baumannii" or "maxtam and baumannii". Randomized controlled trials, controlled clinical studies, and cohort studies were considered for inclusion. The primary outcome was the clinical response rate for sulbactam-based therapy vs comparator therapies. RESULTS: Four studies (1 prospective, 3 retrospective) were included in the metaanalysis. Sulbactam was given in combination with ampicillin, carbapenem, or cefoperazone (n = 112 participants). Comparator drugs included colistin, cephalosporins, anti-pseudomonas penicillins, fluoroquinolones, minocycline/doxycycline, aminoglycosides, tigecycline, polymyxin, imipenem/cilastatin, and combination therapy (n = 107 participants). The combined clinical response rate odds ratio did not significantly favor sulbactam-based therapy over comparator therapy (odds ratio = 1.054, 95% confidence interval = 0.550-2.019, p = 0.874), nor did any of the individual study odds ratios. CONCLUSIONS: The available evidence suggests that sulbactam-based therapy may be similarly efficacious to alternative antimicrobial therapies for the treatment of A. baumannii infection. Further research on this issue is warranted given the limited availability of data from high quality/randomized controlled trials.